Cerebrospinal Fluid Flow Analysis in Prepontine Cistern, Foramen Magnum and 5th Cervical Spine Levels: Temporal and Spatial Patterns at MR Imaging in Volunteers and in Patients with Chiari I Malformation: Cerebrospinal Fluid Flow Analysis in Prepontine Cistern, Foramen Magnum and 5th Cervical Spine Levels: Temporal and Spatial Patterns at MR Imaging in Volunteers and in Patients with Chiari I Malformation - Wirojtananugoon, Chewarat; Somtua, Parichart; Sangkarat, Witaya; Boongerd, Attaporn; Techavipoo, Udomchai (The ASEAN Journal of Radiology, 2025)
Background and Purpose: The neurological signs and symptoms in Chiari I malformation patients are related to cerebrospinal fluid (CSF) flow obstruction at the foramen magrum. Previous studies show signilicantly higher peak CSF velocity at the foramen magnum level in these patients than in the normal population. However, recent studies report no significant difference of peak CSF velocity at the foramen magnum between symotomatic and asymptomatic Chiari I groups and suggested further studies of CSF flow outside the foramen magnum for better patient classication. The purpose of this study was to evaluate and compare CSF flow patterns in Chiari I patients and in healthy controls at the prepontine cistern, foramen magnum, and 5th cervical spine (C5) levels. Methods: Five patients and ten healthy control volunteers were studled with a phase-contrast MRI at these levels through 20 phases of a cardiac cycle. The CSF flow patterns were analyzed for inhogeity using the flow velocity diffence between the areas anterior and posterior to the spinal cord, the synchronous bidirectional flow, and the preferential flow direction. Results: The peak systolic velocity means in the patients were higher than those in the controls for all three levels: However, statistical signicance occurred only at the foramen magnum level. For all three levels, the flow spatial and temporal variations (flow nodes and jets and consecutive images with synchronous bidirectional flows) were more evident in the patients than in the controls. Conclusion: No significant diffence of the CSF flow occurs at the prepontine cistem and C5 levels between the patients and controls. Therefore, the CSF flow studies outside the foramen magnum may not be effective for patient evaluation